2017
DOI: 10.17148/iarjset.2017.4533
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Compensation and Benefits on Employees’ Performance: A Study of Audit Firms in Bahrain

Abstract: Abstract:The study is about the assessment of compensation and benefits in selected audit firms in the Kingdom of Bahrain. The research study appraised the current status of compensation and benefits of the firms in terms of remuneration, allowance, promotion and incentives. Also, it endeavored to figure out the perceptions of the employees of the selected audit firms in the Kingdom of Bahrain on the level of effectiveness of compensation and benefits along with the same variables in order to establish a base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…This is because, sometimes there are unfair compensation to the employee because of the bias of the manager. The allowances are not provided on fair criteria [2]. Besides, many employees do not understand about the compensation and benefits.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because, sometimes there are unfair compensation to the employee because of the bias of the manager. The allowances are not provided on fair criteria [2]. Besides, many employees do not understand about the compensation and benefits.…”
Section: Problem Statementmentioning
confidence: 99%
“…Prior research has sought to identify a "pay for performance" relationship in executive compensation, but discovered no clear link between presidential salaries and performance measures [8]. However, the poor compensation and benefits will lead to low performance, thus lead to low satisfaction level and increase absenteeism in employee and the outcome will decrease [2]. The organization that manage compensation and benefits of the employee poorly will decrease the motivation of the employee to work harder [9].…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher such as Anitha, (2014) found employee engagement was a significant predictor of employee performance. In addition, this research will be using employee compensation & benefits, which the previous researcher such as Feraro-Banta and Shaikh, (2017) found that there is an important association between employees' compensation and benefits and employee performance in audit firms in Bahrain. Moreover, previous research has also shown that employee recognition and employee performance are correlated.…”
Section: Primary Schools Teachersmentioning
confidence: 99%